Copper-based powder metallurgy friction material and preparation method thereof
By introducing tin sulfide and nickel-coated tungsten disulfide into copper-based powder metallurgy friction materials and optimizing the material composition, the problems of unstable friction coefficient, abnormal wear and severe damage of existing friction materials in high-speed trains were solved, and the effects of high friction coefficient, good stability and low wear were achieved.
Patent Information
- Application Number
- CN202510765483.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-20
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-12
AI Technical Summary
Existing copper-based powder metallurgy friction materials, when used in combination with carbon-ceramic composite materials, have problems such as unstable friction coefficient, abnormal wear and severe damage, especially under the high temperature and high load conditions of high-speed trains.
By introducing appropriate amounts of tin sulfide and nickel-coated tungsten disulfide as lubricating components and combining simple process steps, the composition and properties of copper-based powder metallurgy friction materials are optimized to improve their friction stability and wear resistance in high-speed trains.
The copper-based powder metallurgy friction material achieves high friction coefficient, good stability and low wear under 400km/h high-speed train conditions, meeting the performance requirements of high-speed and high-temperature braking.
Smart Images

Figure CN120624882A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of design and preparation of powder metallurgy friction materials, in particular to a copper-based powder metallurgy friction material and a preparation method thereof. Background Art
[0002] The higher operating speeds of high-speed trains place higher performance demands on friction materials. Cast steel brake discs, for example, are prone to thermal cracking and increased wear, among other issues. Carbon-ceramic composites, with their superior properties such as lightweight, high-temperature resistance, and high wear resistance, are expected to replace cast steel in high-speed train brake disc applications. However, when the brake disc material transitions from cast steel to carbon-ceramic composites, the accompanying copper-based powder metallurgy friction material can suffer from performance issues such as unstable friction coefficients, abnormal wear, and severe damage. Therefore, it is necessary to optimize existing copper-based powder metallurgy friction materials to meet the requirements of carbon-ceramic composites.
[0003] Copper-based powder metallurgy friction materials primarily consist of a copper matrix, friction components (such as iron, ferrochrome, zirconium oxide, silicon oxide, and silicon carbide), and lubricating components (such as molybdenum disulfide and graphite). In this material system, the friction components provide a high friction coefficient and wear resistance, while the lubricating components reduce the friction coefficient and lubricity. The copper matrix supports these two components, achieving a synergistic effect of friction and lubrication, resulting in copper-based powder metallurgy friction materials with both a high and stable friction coefficient and wear resistance. However, due to the large variations in surface uniformity, the presence of more hard micro-asperities on the surface, and low thermal conductivity, carbon-ceramic composites can cause greater damage to copper-based powder metallurgy friction materials.
[0004] The main current solutions to these problems involve alloying the matrix and modifying ceramic particles. Patent CN112371972A uses copper-nickel alloy powder instead of electrolytic copper powder, which can meet the 350 km / h braking standard. However, the copper-nickel alloy strengthens the copper powder, resulting in insufficient sintering performance and reduced mechanical bonding between the components. Therefore, braking performance at higher speeds is unknown.
[0005] Patents CN117904482A, CN11961912A, and CN116287849A all report the use of composite ceramic components such as sepiolite and zirconium oxide-titanium nitride composite ceramic powders to introduce copper-based powder metallurgy friction materials. Importantly, the addition of ceramic components easily promotes the oxidation of the friction material surface to form a ceramic composite layer, which can easily lead to a low friction coefficient at high temperatures and insufficient braking performance. Therefore, the braking conditions mentioned in these patents are 24 m / s, 0.45 or 0.35 inertia, and a friction material area of 2240 mm. 2 Energy density is about 40 J / mm 2 , which only corresponds to 100km / h. This has limited reference significance for the development of copper-based friction materials that can meet the requirements of 400km / h with carbon ceramics.
[0006] As can be seen from the above, existing research and invention technologies have focused on using complex alloy powders and ceramic composite powders to improve the friction coefficient and wear resistance of copper-based powder metallurgy friction materials. However, due to limitations in testing technology, testing conditions have not reached 400 km / h. Because the copper matrix requires good synergy with the metal, ceramic friction components, and lubricating components, it is important to note that there are no reports on metal coating of the minimal lubrication component to achieve performance improvements in copper-based powder metallurgy friction materials. Summary of the Invention
[0007] The present invention is the first to attempt to develop a copper-based powder metallurgy friction material for high-speed train carbon-ceramic accessories using trace components of tin sulfide and nickel-coated tungsten disulfide.
[0008] The present invention is based on Chinese patent CN201610962043.7 and optimizes and develops a copper-based powder metallurgy friction material with excellent performance and fully meeting the 400km / h friction braking requirements through a simple process.
[0009] The present invention improves the friction stability and wear resistance of copper-based friction materials by combining the sintered product of tin sulfide and nickel-coated tungsten disulfide in appropriate amounts and proportions, and by enhancing their high-temperature lubricity. By combining the appropriate amounts and proportions of tin sulfide and tungsten disulfide with other appropriate components, the present invention achieves a copper-based powder metallurgy friction material that fully meets the requirements of 400 km / h friction braking.
[0010] The present invention discloses a copper-based powder metallurgy friction material. The raw material components used in the material are composed of the following components in percentage by mass: 45-55% of copper powder, 8-20% of iron powder, 6-15% of ferrochrome, 16-22% of graphite, 0.5-4% of molybdenum disulfide, 0.5-4% of tin sulfide, and 0.5-4% of nickel-coated tungsten disulfide, wherein the mass ratio of tin sulfide to nickel-coated tungsten disulfide is 1-2:1-2; the nickel content in the nickel-coated tungsten disulfide is 5-40%; and the total amount of molybdenum disulfide, nickel-coated tungsten disulfide, and tin sulfide is less than or equal to 5%.
[0011] The present invention discloses a copper-based powder metallurgy friction material, which is obtained by combining tin sulfide and tungsten disulfide in appropriate amounts and proportions with other components, and can better adapt to carbon-ceramic composite materials to ensure reliability under high-speed and high-temperature braking.
[0012] Preferably, the tin sulfide particle size range is less than 100 mesh.
[0013] Preferably, the particle size range of nickel-coated tungsten disulfide is less than 100 mesh.
[0014] Preferably, the present invention provides a copper-based powder metallurgy friction material for high-speed train carbon-ceramic fittings and a preparation method thereof, wherein the purity of tin sulfide is greater than 99.5%, and the purity of nickel-coated tungsten disulfide is greater than 99.7%.
[0015] Among the raw materials used, the total amount of sulfides (molybdenum disulfide, nickel-coated tungsten disulfide, and tin sulfide) is no more than 5%, because the sintering diffusion and reaction of sulfides with the copper matrix need to be controlled. If the amount is too much, the presence of excessive sulfides will accelerate the reaction between copper and sulfides in the sintering process, reduce the copper content and material uniformity, and other problems.
[0016] Further preferably, the present invention provides a copper-based powder metallurgy friction material, the raw material components of which are composed of the following components in mass percentage: 50-54% copper powder, 16-19% iron powder, 7-10% ferrochrome powder, 16-20% graphite, 1-1.5% molybdenum disulfide, 0.5-1.5% tin sulfide, and 0.5-1.5% nickel-coated tungsten disulfide.
[0017] Furthermore, the present invention provides a copper-based powder metallurgy friction material comprising the following raw material components, calculated by mass percentage: 53% copper powder, 18% iron powder, 8% ferrochrome powder, 18% graphite, 1% molybdenum disulfide, 1% tin sulfide, and 1% nickel-coated tungsten disulfide. The resulting copper-based powder metallurgy friction material exhibits improved friction curve stability and significantly reduced wear. Its performance is particularly superior when used on high-speed, heavy-load equipment running at speeds of 400 km / h.
[0018] In the present invention, the particle size of the copper powder is 200-300 mesh.
[0019] In the present invention, the particle size of the iron powder is 200-300 meshes.
[0020] In the present invention, the particle size of the ferrochrome powder is less than 200 meshes.
[0021] In the present invention, the particle size of graphite is 10-100 meshes.
[0022] In the present invention, the particle size of nickel-coated molybdenum disulfide is 100-200 meshes.
[0023] In the present invention, the ferrochrome is preferably low carbon ferrochrome.
[0024] As a further preference, in the low carbon ferrochrome, Cr ≥ 52wt%, C ≤ 0.06wt%, and Fe as the balance.
[0025] Preferably, the nickel content in nickel-coated tungsten disulfide is 5-10%.
[0026] The present invention provides a method for preparing a copper-based powder metallurgy friction material, comprising the following steps:
[0027] (1) Raw material mixing: Copper powder, iron powder, ferrochrome powder and graphite powder are mixed according to the designed composition; molybdenum disulfide, nickel-coated tungsten disulfide and tin sulfide are mixed according to the designed composition; the two mixed powders are mixed again and then kerosene (3-5% of the total mass of the powder) is added, and mixed by a roller to obtain a uniform powder.
[0028] (2) Compression molding: Add the powder mixed evenly in (1) into the mold and obtain the formed blank by cold pressing.
[0029] (3) Pressure sintering: The formed blank obtained in (2) is placed in a pressure sintering furnace under a protective atmosphere at a sintering temperature of 900-950°C, a pressure of 1.5-2 MPa, and a holding time of 2-3 hours. The copper-based powder metallurgy friction material is then obtained by cooling in the furnace.
[0030] The particle size range of tin sulfide is less than 100 mesh, and the particle size range of nickel-coated tungsten disulfide is less than 100 mesh. The particle size of both powders is smaller than that of molybdenum disulfide. Through the mixing process, the two fine particles can be dispersed within the coarse particles to ensure the uniform distribution of the sulfides. Too large a particle size will result in insufficient reaction with the copper matrix, while too small a particle size will result in excessive reaction, making it impossible to guarantee both the reaction products and the original structure of the original tungsten disulfide, tin sulfide, and molybdenum disulfide. It can improve the interfacial bonding between the copper matrix and the sulfide, as well as the high-temperature lubrication effect of the sulfide itself. The introduction of tin enables solid solution strengthening of the copper matrix, and the introduction of tungsten improves the high-temperature wear resistance of the copper matrix.
[0031] As a preferred embodiment, nickel-coated tungsten disulfide in the present invention is prepared by the following steps:
[0032] Tungsten disulfide powder is dispersed in deionized water at a concentration of 5–35 g / L and stirred to obtain a uniform suspension. A 0.01–0.05 mol / L nickel nitrate solution is added at a volume ratio of 1:(0.9–1.0) to the suspension. A 0.01–0.05 mol / L reducing agent (sodium borohydride solution) is added dropwise at a volume ratio of 1:(2–2.5) to the suspension, and nickel ions are reduced and deposited under stirring. To ensure reaction efficiency and deposition uniformity, the pH of the system is adjusted to 8–9, and the reaction is carried out at 40–70°C for 1–2 hours. After the reaction is complete, the product is washed several times with deionized water to remove residual impurities and then dried under vacuum or an inert atmosphere to obtain nickel-coated tungsten disulfide powder.
[0033] In the present invention, the amount of the reducing agent used is 1.0 times or more of the theoretical amount for completely reducing the nickel in the nickel salt.
[0034] The present invention designs and prepares a copper-based powder metallurgy friction material for carbon-ceramic fittings of high-speed trains and a preparation method thereof. In step (2), the cold pressing pressure is 25-30 MPa and the holding time is 2-5 s.
[0035] The present invention designs and prepares a copper-based powder metallurgy friction material for carbon-ceramic fittings of high-speed trains and its preparation method. The obtained product has an open porosity of <8% and a density of >4.8 g / cm 3 , Brinell hardness> 17HB.
[0036] The present invention designs and prepares a copper-based powder metallurgy friction material for carbon-ceramic fittings of high-speed trains and its preparation method. Under the working conditions simulating emergency braking conditions at 400 km / h, the friction coefficient of the obtained product is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear loss is 0.05 to 0.10 cm 3 / MJ. Under the working condition of simulating 200km / h emergency braking conditions, the friction coefficient of the obtained product is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear volume is 0.01 to 0.02 cm 3 The product obtained by the present invention has a high friction stability coefficient and a greatly reduced wear amount, meeting the standard requirements.
[0037] The present invention uses nickel-coated tungsten disulfide and tin sulfide in appropriate amounts and proportions, which can, on the one hand, improve the strength of the copper-based powder metallurgy friction material matrix, cleverly introduce metal element reinforcement materials, and improve the friction coefficient and wear resistance; on the other hand, it can utilize the high-temperature lubrication properties of tungsten disulfide and tin sulfide to significantly improve friction stability; the preparation process of the present invention is simple and efficient, and the overall strength of the copper-based powder metallurgy friction material is improved, and the friction stability coefficient and wear resistance are improved.
[0038] Beneficial effects
[0039] The present invention utilizes appropriate amounts and proportions of nickel-coated tungsten disulfide and tin sulfide to enhance the strength of the copper-based powder metallurgy friction material matrix, cleverly introducing metal element reinforcement to improve the friction coefficient and wear resistance. Furthermore, the high-temperature lubrication properties of tungsten disulfide and tin sulfide are utilized to significantly enhance friction stability. The present invention features a simple and efficient preparation process, and improves the overall strength, friction stability, and wear resistance of the copper-based powder metallurgy friction material. Compared to existing copper-based powder metallurgy friction materials that do not utilize multiple sulfide reinforcements, the present invention exhibits superior compatibility.
[0040] The high-wear-resistant copper-based powder metallurgy friction material provided by the present invention has less surface damage and minimal damage to the mating parts during the braking process, has a high friction coefficient, stable braking performance, and excellent wear resistance. It does not require additional pretreatment of the powder, has a simple and efficient preparation process, and does not use environmentally unfriendly raw materials.
[0041] The highly wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention exhibits excellent performance under simulated 400km / h emergency braking conditions, and is particularly far superior to the products obtained by the prior art. When the product obtained by combining appropriate amounts and proportions of nickel-coated tungsten disulfide and tin sulfide with other components is applied to 400km / h emergency braking, the reaction between the copper matrix and nickel and tin during the sintering process strengthens the matrix and component interfaces, achieves an in-situ pinning effect, and improves wear resistance; on the other hand, it protects the reaction loss of tungsten disulfide and ensures high-temperature lubricity. If non-coated tungsten disulfide powder is used, it is easy to cause a violent reaction between copper and tungsten disulfide and tungsten precipitation, reducing the quality of tungsten disulfide and introducing too much hard phase, which is easy to cause fatigue wear and damage. If the ratio is unbalanced, it will lead to deviations in sintering reaction and diffusion, reduce material uniformity, and reduce comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a physical picture of the product obtained in Example 1;
[0043] Figure 2 This is the curve of the product obtained in Example 1 under a simulated 400 km / h braking test;
[0044] Figure 3 This is the curve of the product obtained in Example 2 under a simulated 400 km / h braking test;
[0045] Figure 4 This is the curve of the product obtained in Comparative Example 1 under a simulated 400 km / h braking test. DETAILED DESCRIPTION
[0046] An embodiment of the present invention provides a copper-based powder metallurgy friction material for high-speed train carbon-ceramic pairing and a preparation method thereof. By pairing with carbon-ceramic, the material can simulate 400 km / h emergency braking conditions and exhibit excellent braking performance.
[0047] The test machine used in the present invention to simulate 400km / h braking is MM3000 test machine, with an actual speed of 6400 rpm and an inertia of 1.035 kg×m 2 ; Friction area is 3.7mm 2 , the energy density acting on the friction material is 617.28J / mm 2 The braking parameters calculated for the simulated 200 km / h braking method are consistent with those for the simulated 400 km / h braking method, except for the actual speed of 3200 rpm.
[0048] The performance of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0049] Example 1
[0050] (1) Preparation of nickel-coated tungsten disulfide: 45.8 g of tungsten disulfide powder was dispersed in 1.5 L of deionized water and stirred to obtain a uniform suspension. 1.43 L of a 0.05 mol / L nickel nitrate solution was added, and 3.58 L of a 0.02 mol / L reducing agent (sodium borohydride solution) was added dropwise to perform reduction deposition of nickel ions under stirring. To ensure reaction efficiency and deposition uniformity, the pH of the system was adjusted to 8, and the reaction was carried out at a temperature of 55 ° C for 90 min. After the reaction was completed, the mixture was washed with deionized water several times to remove residual impurities, and then dried in an inert atmosphere to obtain 48.9 g of nickel-coated tungsten disulfide powder.
[0051] (2) Raw material mixing: According to the designed components (mass percentage), 53% copper powder (particle size: 150 mesh ~ 300 mesh), 18% iron powder (particle size: 200 ~ 300 mesh), 8% ferrochrome powder (particle size: -200 mesh), 18% graphite (particle size: 50 ~ 100 mesh) are mixed manually; 1% molybdenum disulfide (particle size: 100 ~ 200 mesh), 1% tin sulfide (particle size: less than 100 mesh), 1% nickel-coated tungsten disulfide (particle size: less than 100 mesh); then add 5% kerosene of the total mass of the powder and mix it through a roller to obtain a uniform powder.
[0052] (3) Pressing: The powder mixed in (2) was added to the mold and cold pressed to obtain a blank with an outer diameter of 75 mm and an inner diameter of 53 mm. The cold pressing pressure was 29 MPa and the holding time was 3 s.
[0053] () Pressure sintering: The formed blank obtained in (3) was placed in a pressure sintering furnace under H2 protective atmosphere. The sintering temperature was 950℃, the pressure was 2MPa, and the holding time was 2.5 hours. The copper-based powder metallurgy friction material was then cooled in the furnace and the friction area was processed to 3.7mm. 2 .
[0054] (5) Test results:
[0055] The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.0% and a density of 4.95g / cm 3 , Brinell hardness is 18 HB.
[0056] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.38, a friction stability coefficient of 0.90, and a wear loss of 0.05 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.93, and the wear volume is 0.011 cm3 / MJ.
[0057] Example 2
[0058] The conditions are the same as those in Example 1, except that: 0.7% tin sulfide (particle size: less than 100 mesh), 1.3% nickel-coated tungsten disulfide (particle size: less than 100 mesh);
[0059] (5) Test results:
[0060] The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.3% and a density of 4.91 g / cm 3 , Brinell hardness is 19 HB.
[0061] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.37, a friction stability coefficient of 0.92, and a wear loss of 0.06 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.93, and the wear volume is 0.013 cm 3 / MJ.
[0062] From Examples 1 and 2, it can be seen that in the present invention, by controlling the type and content of sulfide, the copper-based powder metallurgy friction material can have a high friction coefficient and high stability when paired with a carbon-ceramic composite material.
[0063] Example 3
[0064] The conditions are the same as those in Example 1, except that: 1.3% tin sulfide (particle size: less than 100 mesh), 0.7% nickel-coated tungsten disulfide (particle size: less than 100 mesh);
[0065] (5) Test results:
[0066] The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 6.5% and a density of 4.97 g / cm 3 , Brinell hardness is 21 HB.
[0067] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.35, a friction stability coefficient of 0.85, and a wear loss of 0.06 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.36, the friction stability coefficient is 0.88, and the wear volume is 0.015 cm 3 / MJ.
[0068] Example 4
[0069] The conditions are the same as those in Example 1, except that: 0.85% tin sulfide (particle size: less than 100 mesh), 1.15% nickel-coated tungsten disulfide (particle size: less than 100 mesh);
[0070] (5) Test results:
[0071] The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.0% and a density of 4.95g / cm 3 , Brinell hardness is 20 HB.
[0072] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.36, a friction stability coefficient of 0.88, and a wear loss of 0.08 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ. Under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.37, the friction stability coefficient is 0.88, and the wear volume is 0.014 cm 3 / MJ.
[0073] Example 5
[0074] The conditions are the same as those in Example 1, except that: 1.15% tin sulfide (particle size: less than 100 mesh), 0.85% nickel-coated tungsten disulfide (particle size: less than 100 mesh);
[0075] (5) Test results:
[0076] The high wear-resistant copper-based powder metallurgy friction material obtained in this embodiment has an open porosity of 7.3% and a density of 5.00 g / cm 3 , Brinell hardness is 22 HB.
[0077] The high wear-resistant copper-based powder metallurgy friction material designed and prepared by the present invention has a friction coefficient of 0.37, a friction stability coefficient of 0.91, and a wear loss of 0.07 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.35, the friction stability coefficient is 0.91, and the wear volume is 0.017 cm 3 / MJ.
[0078] Comparative Example 1
[0079] Other conditions are the same as those in Example 1, except that: 1% tin sulfide (particle size: less than 100 mesh), 1% non-coated tungsten disulfide (particle size: less than 100 mesh);
[0080] (5) Test results:
[0081] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 9.0% and a density of 4.84 g / cm 3 , Brinell hardness is 25 HB.
[0082] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.28, a friction stability coefficient of 0.77, and a wear loss of 0.17 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.24, the friction stability coefficient is 0.78, and the wear volume is 0.03 cm 3 / MJ.
[0083] Subsequent research found that the lack of tungsten disulfide coating resulted in excessive reaction between tungsten disulfide and the copper matrix to form tungsten and copper sulfide, increasing the material's hardness. This reduced the initial contact area and reduced adhesive wear at high hardness. Consequently, due to frictional heat accumulation, the friction coefficient increased during the later stages of braking, resulting in reduced braking stability. Therefore, the role of nickel-coated tungsten disulfide is very significant.
[0084] Comparative Example 2
[0085] Other conditions are the same as those in Example 1, except that tin sulfide is 0% (particle size is less than 100 mesh), nickel-coated tungsten disulfide is 2% (particle size is less than 100 mesh)
[0086] (5) Test results:
[0087] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 8.4% and a density of 4.91 g / cm 3 , Brinell hardness is 25 HB.
[0088] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.28, a friction stability coefficient of 0.72, and a wear loss of 0.22 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.26, the friction stability coefficient is 0.73, and the wear volume is 0.025 cm 3 / MJ.
[0089] Comparative Example 3
[0090] Other conditions are the same as those in Example 1, except that tin sulfide is 2% (particle size is less than 100 mesh), nickel-coated tungsten disulfide is 0% (particle size is less than 100 mesh)
[0091] (5) Test results:
[0092] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has an open porosity of 7.7% and a density of 4.96 g / cm 3 , Brinell hardness is 21 HB.
[0093] The high wear-resistant copper-based powder metallurgy friction material obtained in this comparative example has a friction coefficient of 0.31, a friction stability coefficient of 0.84, and a wear loss of 0.13 cm under the working condition of simulating the emergency braking condition of 400 km / h. 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.31, the friction stability coefficient is 0.68, and the wear volume is 0.022 cm 3 / MJ.
[0094] Comparative Example 4
[0095] (1) Other conditions are the same as those in Example 1, except that copper powder 51% (particle size: 150-300 mesh), tin sulfide 2% (particle size: 100-150 mesh), nickel-coated tungsten disulfide 2% (particle size: 100-200 mesh)
[0096] The friction material in this comparative example has an open porosity of 7.9% and a density of 4.83 g / cm 3 , Brinell hardness is 19 HB.
[0097] The friction material in this comparative example simulates the working conditions of 400km / h emergency braking, and the friction coefficient is 0.24, the friction stability coefficient is 0.93, and the wear volume is 0.08cm 3 / MJ; under the working condition of simulating emergency braking at 200km / h, the friction coefficient is 0.21, the friction stability coefficient is 0.91, and the wear volume is 0.014 cm 3 / MJ.
[0098]
[0099]
[0100] The embodiments and comparative examples of the present invention are only provided to further illustrate the present invention in detail.
Claims
1. A copper-based powder metallurgy friction material, characterized by: The raw material components used are composed of the following components in percentage by mass: 45-55% of copper powder, 8-20% of iron powder, 6-15% of ferrochrome, 16-22% of graphite, 0.5-4% of molybdenum disulfide, 0.5-4% of tin sulfide, and 0.5-4% of nickel-coated tungsten disulfide, and the mass ratio of tin sulfide to nickel-coated tungsten disulfide is 1-2:1-2; the nickel content in the nickel-coated tungsten disulfide is 5-40%; and the total amount of molybdenum disulfide, nickel-coated tungsten disulfide, and tin sulfide is less than or equal to 5%.
2. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size range of tin sulfide is less than 100 mesh; the particle size range of nickel-coated tungsten disulfide is less than 100 mesh.
3. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The purity of tin sulfide is >99.5%, and the purity of nickel-coated tungsten disulfide is >99.7%.
4. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The raw material components used are calculated by mass percentage and consist of the following components: 50-54% copper powder, 16-19% iron powder, 7-10% ferrochrome powder, 16-20% ferrochrome powder, 1-1.5% molybdenum disulfide, 0.5-1.5% tin sulfide, and 0.5-1.5% nickel-coated tungsten disulfide.
5. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The raw material components used are calculated by mass percentage and consist of the following components: 53% copper powder, 18% iron powder, 8% ferrochrome powder, 18% graphite, 1% molybdenum disulfide, 1% tin sulfide, and 1% nickel-coated tungsten disulfide.
6. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The particle size of copper powder is 200-300 mesh; the particle size of iron powder is 200-300 mesh; the particle size of ferrochrome powder is less than 200 mesh; the particle size of graphite is 10-100 mesh; the particle size of molybdenum disulfide is: 100-200 mesh.
7. A method for preparing the copper-based powder metallurgy friction material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Raw material mixing: Copper powder, iron powder, ferrochrome powder, and graphite powder are mixed according to the designed composition; molybdenum disulfide, nickel-coated tungsten disulfide, and tin sulfide are mixed according to the designed composition; the two mixed powders are mixed again and then kerosene (3-5% of the total mass of the mixed powder) is added, and mixed by a roller drum to obtain a uniform powder; (2) Compression molding: Add the powder mixed evenly in (1) into the mold and obtain the formed blank by cold pressing; (3) Pressure sintering: The formed blank obtained in (2) is placed in a pressure sintering furnace under a protective atmosphere at a sintering temperature of 900-950°C, a pressure of 1.5-2 MPa, and a holding time of 2-3 hours. The copper-based powder metallurgy friction material is then obtained by cooling in the furnace.
8. The method for preparing a copper-based powder metallurgy friction material according to claim 7, characterized in that: Nickel coated tungsten disulfide is prepared by the following steps: Tungsten disulfide powder is dispersed in deionized water at a concentration of 5-35 g / L and stirred to obtain a uniform suspension; nickel nitrate with a concentration of 0.01-0.05 mol / L is added as a nickel salt solution, and 0.01-0.05 mol / L of a reducing agent is added dropwise to perform reduction deposition of nickel ions under stirring conditions; during reduction, the system pH value is controlled at 8-9, the reaction temperature is controlled at 40℃-70℃, and the reaction time is controlled at 1-2h; after the reaction is completed, it is washed with deionized water and then dried in a vacuum or inert atmosphere to obtain nickel-coated tungsten disulfide powder.
9. The method for preparing a copper-based powder metallurgy friction material according to claim 7, characterized in that: In step (2), the cold pressing pressure is 25-30 MPa and the holding time is 2-5 s.
10. The method for preparing a copper-based powder metallurgy friction material according to claim 7, characterized in that: Under the working conditions simulating 400km / h emergency braking conditions, the friction coefficient of the obtained copper-based powder metallurgy friction material is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear volume is 0.05 to 0.10 cm 3 / MJ; under the working condition simulating the emergency braking condition of 200km / h, the friction coefficient of the obtained copper-based powder metallurgy friction material is between 0.35 and 0.40, the friction stability coefficient is greater than 0.8, and the wear volume is 0.01 to 0.02 cm 3 / Between MJ.
Citation Information
Patent Citations
Super-simple component powder metallurgy friction material for high-speed train brake pad
CN106399743A
Powder metallurgy brake pad lining friction body for carbon-ceramic brake disc of motor train unit and preparation method thereof
CN112371972A
Copper-based friction material paired with carbon ceramic plate and preparation method of copper-based friction material
CN116287849A
Cited By
A partition-strengthened compound structure cam for a compound needle circular weft knitting machine and a forming method thereof
CN121339448B
Powder metallurgy material and preparation method thereof, friction pair part and suspension gear pump
CN121518963A